Tinjauan Yuridis Pembatalan Kelulusan Pelamar dalam Pengadaan Pegawai Negeri Sipil karena Ketidaksesuaian Kualifikasi Pendidikan - Risang Pujiyanto; Sonny Taufan; Rr Gumilar Tw (LITERATUS, 2022)
This study has the aim of analyzing the cancellation of the graduation status of Civil Servant procurement applicants whose educational qualifications are not in accordance with those that have been established and only known in the future. This research uses normative legal research methodology with a statute approach. The results of the study found that Government Regulation Number 11 of 2017 concerning Management of Civil Servants as amended by Government Regulation Number 17 of 2020 only regulates the dismissal of Candidates for Civil Servants and does not explicitly regulate the cancellation of graduation. The provisions in Government Regulation Number 11 of 2017 mutatis mutandis apply to the cancellation of the graduation status of applicants who have educational qualifications that do not match, with the limitation that applicants have provided incorrect information regarding their educational qualifications. The principle of contrario actus stipulates that the Staffing Officer is the official authorized to revoke/cancel a decision due to a substance defect in the form of a factual discrepancy regarding educational qualifications caused by the applicant. However, the cancellation of the applicant's graduation cannot be done if the incompatibility of educational qualifications is caused by the inaccuracy of the Civil Service Procurement Committee. This is because there is the principle of mistakes made by State Administrative Officials in issuing decisions that cannot result in losses for justice seekers/society.